2013
DOI: 10.1002/ppul.22839
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and respiratory symptoms in children: The generation R study

Abstract: These results suggest that physical activity may not play an important role in the development of respiratory symptoms in pre-school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Following this meta-analysis, two additional studies have been published 1415 The first did not find that PA was associated with wheezing or shortness of breath in children 14. The second, which followed 1369 children to adulthood, found a possible beneficial effect of PA on the development of respiratory symptoms (OR 0.97, 95% CI 0.95 to 0.99) 15…”
Section: Discussionmentioning
confidence: 99%
“…Following this meta-analysis, two additional studies have been published 1415 The first did not find that PA was associated with wheezing or shortness of breath in children 14. The second, which followed 1369 children to adulthood, found a possible beneficial effect of PA on the development of respiratory symptoms (OR 0.97, 95% CI 0.95 to 0.99) 15…”
Section: Discussionmentioning
confidence: 99%
“…Using the ROBINS‐E tool, included studies were found to contain low‐to‐moderate levels of overall bias. Additionally, studies scored five, six, seven or eight out of nine points on the NOS, indicating moderate‐to‐high quality; hence, all studies were included in this review. Individual quality assessment scores are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies assessed the relationship between PA and asthma‐related outcomes (Table ). All of these studies were conducted in high‐income countries, namely Norway, the Netherlands, Germany, USA and Canada .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations